Pengaruh Self-Efficacy Terhadap Hasil Belajar Matematika Melalui Media Pembelajaran Digital - Jahring; Hasan Djidu (GJET : Global Journal of Educational Technology, 2024)
This study seeks to examine the impact of self-efficacy on mathematics learning outcomes via digital learning media. This research utilized a quantitative method with a descriptive correlational design. The sample comprised 57 tenth-grade pupils chosen by a saturation sampling technique. Data were gathered using a self-efficacy questionnaire employing a 5-point Likert scale consisting of 16 items, along with a curriculum-based assessment of learning outcomes. Regression analysis indicated that self-efficacy significantly affected learning outcomes, with a p-value of 0.044 at a 95% confidence interval. The negative regression coefficient (B = -1.024) suggested that an enhancement in self-efficacy correlated with a decline in students' learning results. This implies that additional factors, such as digital literacy or learning methodologies, may influence the association. These findings underscore the need of a pedagogical approach that not only bolsters self-efficacy but also fosters digital media proficiency to attain optimal learning outcomes